STUDI MORFOMETRIK DAN MORFOLOGI SPERMATOZOA ENAM RUMPUN AYAM LOKAL INDONESIA - Khaeruddin, Khaeruddin -; Hermawansyah, Hermawansyah; Syamsuryadi, Bahri; Junaedi, Junaedi (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2021)
This study aims to determine the morphometric comparison and identify abnormal sperm morphology in six types of Indonesian local chickens. Sperm observed came from six types of local chickens: red jungle fowl, Sentul chicken, Gaga’ chicken, Kampung Unggul Balitnak (KUB) chicken, Arab Silver chicken, and Bangkok chicken. Semen was collected by sequencing technique, then fresh semen was blotted on glass slides with eosin-nigrosine dye. Morphometrics and morphology of sperm were observed using a light microscope with a magnification of 100x16. ImageJ software was used for sperm morphometric observation on 60 sperm cells, while morphological observations were carried out by counting normal and abnormal sperm on 200 sperm cells. The results showed that there were variations in the size of sperm among the six types of chickens. Red jungle fowl had a higher total length and tail length than Sentul, Gaga', KUB, Arab, and Bangkok chickens. Observation of morphological characteristics showed that sperm with the highest abnormal morphology were in red jungle fowl and gaga' chickens. Tail bending and mid-piece bending is the most common abnormalities found in Indonesian local chickens.